2021
DOI: 10.14569/ijacsa.2021.0120462
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Accidents Detection using Geographic Information Systems (GIS)

Abstract: The mission of reducing the number and severity of traffic accidents becomes the dominant target of road traffic safety management worldwide. The main objective of this work is to analyze traffic accidents in temporal and spatial frameworks in the capital city Amman and identify hotspot zones in the study area. Several statistical analyses are conducted using SQL to give insight into the temporal distribution of accidents and to identify the most revealing accidents based on several attributes such as the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The researcher developed a regression model to predict the occurrence of a fatal accident in Ahmedabad city with statistical analysis by collecting the fatal accident data and traffic volume per lane for Place Shahibaug and Karanj Bhadra, Ahmedabad, for the period of six years from 2005 to 2010. The regression model developed was found to be satisfactory with the goodness of fit and with a successful prediction rate [31]. In order to have an organized city, at the planning stage itself, we have to give special attention to vulnerable road users such as pedestrians and cyclists to reduce road accidents.…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…The researcher developed a regression model to predict the occurrence of a fatal accident in Ahmedabad city with statistical analysis by collecting the fatal accident data and traffic volume per lane for Place Shahibaug and Karanj Bhadra, Ahmedabad, for the period of six years from 2005 to 2010. The regression model developed was found to be satisfactory with the goodness of fit and with a successful prediction rate [31]. In order to have an organized city, at the planning stage itself, we have to give special attention to vulnerable road users such as pedestrians and cyclists to reduce road accidents.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Palayamkottai is the central business center located on the eastern bank of the Thamirabarani River. The town has a number of educational institutions and administrative offices like District police headquarters, medical colleges, commercial shops, and hospitals, attracting more traffic from the outskirts of the city, causing high traffic flow in the city [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. The Municipal Corporation Act of 1994 established a municipal corporation to operate Tirunelveli.…”
Section: Study Areamentioning
confidence: 99%
“… 17 , 19–22 A GIS is considered a tool to help prioritize interventions and efficiently allocate resources to improve road safety. 11–15 , 23 , 24 The corrective measures for the causes of road crashes then involve changes in the built environment. 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…17,[19][20][21][22] A GIS is considered a tool to help prioritize interventions and efficiently allocate resources to improve road safety. [11][12][13][14][15]23,24 The corrective measures for the causes of road crashes then involve changes in the built environment. 25,26 In Benin, since 2008, financial investments have been made to acquire Global Positioning System (GPS) receivers and train police officers in charge of road crash reports.…”
Section: Introductionmentioning
confidence: 99%
“…Among few notable contributions towards traffic data analysis, in [3], using road accident data of UK between 2005 and 2019 for finding risk and predicting severity of accidental injuries, authors have used data analytics strategies. It can found in [4] that spatial pattern of accident distribution in a specific study area can be analyzed and accident hot spots are identified using GIS based spatial and statistical analysis tools. In [5], authors present the performance result of spatial analysis of accident prone traffic location classification using Multi-criteria Decision Making (MCDM) approach.…”
Section: Introductionmentioning
confidence: 99%